Transforming Innovation into Success: The Key to Public Entrepreneurship Success in Public Organizations in Indonesia - Haedar Akib (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This article aims to explore the significance of public entrepreneurship in achieving success and fostering innovation within public organizations in Indonesia. The background of the study highlights the growing recognition of the importance of entrepreneurship in the public sector and its potential to drive positive change and deliver better services to citizens. The research objective is to identify the key factors that contribute to the success of public entrepreneurship in Indonesia's public organizations. A qualitative research method, including interviews and case studies, was employed to gather data and analyze the experiences of successful public entrepreneurs. The findings reveal that factors such as leadership support, a conducive innovation ecosystem, collaboration with stakeholders, and a culture of risk-taking and experimentation are vital for the success of public entrepreneurship in Indonesian public organizations. This research provides valuable insights for policymakers, managers, and practitioners in fostering public entrepreneurship and harnessing the transformative power of innovation for the betterment of public service delivery in Indonesia.